Mental Toughness and Associated Personality Characteristics of Marathon des Sables Athletes - Goddard, Keith; Roberts, Claire-Marie; Anderson, Liam; Woodford, Lindsay; Byron-Daniel, James (Frontiers in Psychology, 2019)
Mental toughness (MT) is commonly referred to as an important prerequisite for sustained athletic achievement. The increased research focus on MT has led to the development of a consistent debate centred around whether the construct is a unidimensional or multidimensional trait, and whether it can be differentiated from similar constructs such as hardiness. In order to move towards more clarity of MT, the present study is exploratory in nature, using athletes who have competed in the Marathon des Sables (MdS) ultra-endurance event. The Marathon des Sables is a timed 250km race in the Sahara Desert that takes place over 6 days in temperatures exceeding 40 degrees centigrade. Forty two British MdS competitors were recruited via the UK organising company. Each participant completed the NEO PI-R as a measure of the five major domains of personality, as well as the six traits or facets that define each domain. Additionally, they completed the Sport Mental Toughness Questionnaire (SMTQ). The MdS sample’s NEO PI-R results were compared against general population norms, and results showed a distinct ultra-endurance athlete profile characterised by significantly higher levels of extraversion and openness to experience. Additionally, the MdS sample’s SMTQ scores were higher than the normed sample consisting of a collection of athletes representing multiple sports. Finally, linear regression analyses indicated a convergence between the two measures, supporting the argument that MT may in fact be measured by a general personality questionnaire such as the NEO PI-R.